1996
DOI: 10.1007/bf00024401
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-acetic acid, ethylene, and abscisic acid metabolism in developing muskmelon (Cucumis melo L.) fruit

Abstract: Hormonal metabolism associated with fruit development in muskmelon was investigated by measuring IAA, ABA, and ACC levels in several tissues at various stages of development. In addition, levels of conjugated IAA and ABA were determined in the same tissues. Ethylene production, which is believed to signal the ripening and senescence of mature fruit, was also measured. Ethylene production was highest in the outer tissue near the rind and gradually declined during maturation, except for a dramatic increase in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Therefore the effect of CPPU was not maintained, indicating that normal seeds were important for fruit development. No further information is available about endogenous hormones in melon seeds, although Dunlap et al (1996) has reported about IAA, ethylene and ABA metabolism in developing muskmelon fruit. In earlier studies we reported that CPPU treatment increases endogenous IAA content and decreases endogenous ABA content and also that CPPU promotes invertase activity in seeded melon fruit during the early growth stage (Hayata et al, 2001a).…”
Section: Tablementioning
confidence: 95%
“…Therefore the effect of CPPU was not maintained, indicating that normal seeds were important for fruit development. No further information is available about endogenous hormones in melon seeds, although Dunlap et al (1996) has reported about IAA, ethylene and ABA metabolism in developing muskmelon fruit. In earlier studies we reported that CPPU treatment increases endogenous IAA content and decreases endogenous ABA content and also that CPPU promotes invertase activity in seeded melon fruit during the early growth stage (Hayata et al, 2001a).…”
Section: Tablementioning
confidence: 95%
“…In all four fruit species mentioned above, as well as in many other climacteric and non-climacteric fruit, the application of natural or synthetic auxins during the pre-ripening stage of fruit development has often been found to lead to a ripening delay (reviewed by [ 6 ]) and therefore auxins are widely viewed as ripening inhibitors [ 24 , 26 , 29 , 33 ]. In contrast IAA-amide conjugates have been reported to accumulate in ripening bananas [ 26 ], muskmelons ( Cucumis melo L.) [ 34 ] and strawberries [ 27 ]. More detailed studies in grape berries have revealed that the concentration of IAA-Asp, an IAA-amide conjugate linked to IAA degradation [ 35 ] and formed by the action of IAA-amido synthetases (Gretchen Hagen (GH3) proteins) [ 36 ], increased sharply at veraison and remained at high concentrations throughout the ripening phase [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…IAA-Asp is known to be an endogenous component of soybean seeds (Cohen, 1982), and available evidence indicates that it is present in many other plant species (Row et al, 1961;Olney, 1968;Tillberg, 1974;Andersson and Sandberg, 1982;Cohen and Ernstsen, 1991;Dunlap et al, 1996). However, despite its widespread existence in plants and two hopeful preliminary reports (Lantican and Muir, 1967;Higgins and Barnett, 1976), an in vitro system for IAA-Asp synthesis or hydrolysis by an enzymatic mechanism has yet to be achieved (Bandurski et al, 1995).…”
mentioning
confidence: 99%